PENGARUH PENDIDIKAN, PELATIHAN DAN PENGALAMAN KERJA TERHADAP KOMPETENSI ASUHAN PERSALINAN NORMAL BIDAN - sylvina rahmawati (MNJ (Mahakam Nursing Journal), 2017)
The Influence of Education, Training and Work Experience of the Competency Achievement Midwives in Normal Delivery Care in the Delivery Room Unit dr. H. Slamet Martodirdjo Pamekasan. This research was conducted in dr. Slamet Martodirdjo Pamekasan with a total sample of 35 people. The purpos is determine the effect of simultaneous, partial and dominant influence of independent variables consisting of: education, training and work experience to the dependent variable is the competence of midwives. The results showed that simultaneous, independent variables include: education, training and work experience have a significant effect on the competence of midwives, is evidenced by the value of F arithmetic amounted to 6,501 with significance level of 0.002 (less than 0.05). Partially, education, training and work experience have a significant effect on the competence of midwives, is evidenced by the t value of each independent variable, namely: education T value of 2.340 with a significance level of 0.003, training with t value of 1.950 with a degree of the significance of 0004 and work experience counted for 3,718 t with a significance level of 0001 (less than 0.05). Thus it can be said that all independent variables partially have a significant influence on the Competency Achievement Midwives in Normal Delivery Care in the Delivery Room Unit in dr. H. Slamet Martodirdjo Pamekasan; variable work experience has dominant influence on the Competency Achievement Midwives in Normal Delivery Care in the Delivery Room Unit in dr. H. Slamet Martodirdjo Pamekasan. Keywords: Education (X1), Training (X2), Work Experience (X3) and Competence Midwives (Y).